Preliminary Study on the Reconstruction and Function of the Hyperelongate Neural Spines in the Dorsal Vertebrae of Deinocheirus mirificus (Theropoda: Ornithomimosauria) - Luo, Xin; Liao, Chunchi (Transactions on Social Science, Education and Humanities Research, 2024)
Deinocheirus is a bizarre and unique theropod dinosaur. The holotype of Deinocheirus was discovered in 1976, but its characteristics and phylogenetic position remained largely enigmatic due to the scarcity of fossil material. This changed in 2014 when Lee et al. described two additional specimens, providing a deeper insight into this mysterious creature. Notably, the smaller specimen MPC-D 100/128 preserved a relatively complete dorsal vertebra with hyperelongated neural spines, reaching up to 8.5 times the height of the corresponding centra. This suggests that Deinocheirus possessed a raised dorsal sail or hump-like structure. Elongated neural spines have evolved multiple times in dinosaurs, including in ornithopods of ornithischians as well as theropods and sauropods of saurischians, with various hypothesized functions such as thermoregulation, fat storage, or sexual display. However, previous research on the neural spines of Deinocheirus has been limited to brief description, lacking detailed analysis and leaving the morphology and function of these dorsal structures poorly understood. To better understand the possible dorsal structure of Deinocheirus and its ecological role, this study examines the dorsal neural spines of Deinocheirus and 26 other dinosaurs. Through measurement and comparative analyses, we categorize the height and width of neural spines into different categories. Our comparison reveal that the neural spines of Deinocheirus are most similar to those of Spinosaurus and Ouranosaurus, with a height ratios exceeding 7 and overall morphology closer to the latter. Additionally, the anteroposterior width of neural spines of Deinocheirus is slightly narrower than that of Spinosaurus and Ouranosaurus. Based on these data and previous studies, we infer that the hyperelongated neural spines of Deinocheirus may serve dual functions: supporting a sail related to aquatic habits and a hump associated with an intricate interspinous ligament system, potentially for fat storage to aid in surviving dry seasons. Finally, we discuss avenues for future research, such as bone histology and finite element analysis, which could provide further insights into the morphology and function of the neural spines of Deinocheirus.